Dampak Perjudian Online Slot di Kalangan Pemuda Terhadap Semangat Kerja di Kecamatan Cisalak - Gaha Angun Mangkudilaga; Angger Saloko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to describe the consequences of online slot gambling on the work spirit of youth in Cisalak District, Subang Regency. This study applies a qualitative approach to the form of descriptive research. The data collection methods used included observation and interviews, applying purposive sampling techniques for selecting informants. Data analysis was carried out by adopting an interactive model improved by Miles and Huberman. The results of the study show that young people in Cisalak District have knowledge about online slot gambling, and some of them have fallen into this practice, experiencing dependence which has resulted in decreased morale.